Pengaruh Profitabilitas, Leverage dan Intensitas Modal Terhadap Agresivitas Pajak - Rama Soumokil, Finiko; Budi Yanti, Harti (DINASTI RESEARCH, 2024)
This research aims to analyze the influence of Profitability, Leverage, and Capital Intensity on Tax Aggressiveness. The population in this study was 293 consumer cyclicals and non-consumer cyclicals companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This sample research used a purposive sampling method and obtained a sample of 65 companies. The research results show that ROA has a positive effect on Tax Aggressiveness, Leverage and Capital Intensity have no effect on Tax Aggressiveness.